Sport, doping and female fertility - Sandro La Vignera; Rosita A. Condorelli; Rossella Cannarella; Ylenia Duca; Aldo E. Calogero (BMC, 2018)
Abstract This article is a review that addresses the following topics, divided by paragraphs. The first paragraph investigates the effects of physical activity on ovarian function, analyzing in particular the changes concerning the serum concentrations of follicle-stimulating hormone, luteinizing hormone, prolactin, growth hormone, thyroid hormones, leptin, ghrelin, neuropeptide Y. The second paragraph analyzes the effects of doping on the hypothalamic-pituitary-ovarian axis. Finally, the last paragraph analyzes the PCOS category, evaluating the effects of hyperandrogenism in relation to athletic performance.